1988
DOI: 10.1128/jb.170.11.5392-5395.1988
|View full text |Cite
|
Sign up to set email alerts
|

Lipid modification of Escherichia coli penicillin-binding protein 3

Abstract: . 191:1-9, 1983). An amino acid sequence of Leu-26-Leu-Cys-Gly-Cys-30 was found near the amino terminus of the deduced sequence, showing a rather striking homology to the Leu-Leu-Ala-Gly-Cys consensus sequence for the modification and processing of precursors of the E. coli murein lipoprotein and other bacterial lipoproteins. As (29), and the membrane-bound penicillinases of gram-positive bacteria (15,24,25,30). The precursor forms of these lipoproteins share a common modificationprocessing pathway by virtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 38 publications
2
30
0
Order By: Relevance
“…The construction of a water-soluble active PBP 2x derivative (PBP 2x*) proves once more that the only membraneanchoring region of high-Mr PBPs is the N-terminal hydrophobic peptide domain, and that this peptide is apparently not necessary for enzymatic activity with the possible exception of E. coli PBP 3 (Hayashi et al, 1988). That the water-soluble PBP 2x* appeared perfectly stable over several months is further support for the structural independence of the hydrophilic main part of the PBP.…”
Section: Discussionmentioning
confidence: 97%
“…The construction of a water-soluble active PBP 2x derivative (PBP 2x*) proves once more that the only membraneanchoring region of high-Mr PBPs is the N-terminal hydrophobic peptide domain, and that this peptide is apparently not necessary for enzymatic activity with the possible exception of E. coli PBP 3 (Hayashi et al, 1988). That the water-soluble PBP 2x* appeared perfectly stable over several months is further support for the structural independence of the hydrophilic main part of the PBP.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, if we assume multiple acylations of a fraction of spiralin, the other major fraction of spiralin molecules will stay integrated without the help of any acyl chain since, in S. melliferum, the whole spiralin fraction is bound to the cell membrane. Interestingly, in E. coli, less than 15% of the lipoprotein PBP3 (penicillin-binding protein 3) in the cytoplasmic membrane is modified with acyl chains (16). Whatever the actual situation, it is very probable that the covalent binding of hydrophobic chain(s) to spiralin strengthens the anchoring of the protein within the lipid bilayer.…”
Section: Resultsmentioning
confidence: 99%
“…This would explain the water-insoluble character of this part of the protein. The 21-kDa membrane-associated protein p21 of the ras oncogene family is water-soluble without its C-terminal ester-bound single 16:0 acyl chain but insoluble (or membrane attached) with the chain (13,26).…”
Section: Resultsmentioning
confidence: 99%
“…The N-terminal region seemed to serve for insertion into the membrane: artificial removal of the N-terminal 40 residues resulted in accumulation of the protein in the cytoplasm (3). In the N-terminal region there is a pentapeptide with an amino acid sequence similar to the consensus for bacterial lipoproteins; this pentapeptide was shown, for a minor fraction of the molecules, to actually undergo the lipid modification and probably the processing (22). However, further investigations with gene manipulation to produce hybrid and truncated PBP 3 molecules (20) and with peptide mapping and amino acid sequence analysis of purified precursor and mature forms (42) revealed that cleavage of the C-terminal 11 residues, rather than that of the N-terminal signal peptide, is responsible for the maturation detected as a change in electrophoretic mobility.…”
mentioning
confidence: 99%